Rice Husk Biochar and Foliar Fertilizer Application in Improving Growth and Production of Patchouli Plants (Pogostemon cablin Benth) - Eliza Mayura; Bambang Hariyanto; Neneng Ratna Purnamasari; Herwita Idris; Rasiska Tarigan; Rina C. Hutabarat (Universitas Panji Sakti, 2026)
Patchouli (Pogostemon cablin Benth) is a major essential oil crop widely used in pharmaceutical, perfumery, and aromatherapy industries. Despite Indonesia supplying most of the global demand, productivity and oil quality remain inconsistent across production regions. Although rice husk biochar and foliar fertilizers are individually known to enhance plant growth, their synergistic interaction and optimal combined dosage for patchouli production have not been clearly established, representing an important research gap. This study represents the first experimental attempt to determine the optimal combined dosage of rice husk biochar and foliar fertilizer for improving patchouli growth and oil yield. A Randomized Complete Block Design with two factors (three biochar levels and three foliar fertilizer levels) and 3 replicates was implemented from June to December 2023 in West Sumatra, Indonesia. Significant interaction effects were observed across major growth and yield parameters. The combination of 200 g plant⁻¹ biochar and 1 ml L⁻¹ foliar fertilizer produced the highest biomass accumulation and oil yield compared with other treatments. These findings provide empirical evidence of a synergistic fertilization effect and offer a cost-efficient nutrient management strategy to enhance patchouli productivity under smallholder farming conditions.